CHARACTERISTIC OF (AgI)0.44 (LiI)0.22 (AgPO3)0.34 IONIC CONDUCTOR PREPARED BY MELT QUENCHING METHOD - Makhsun Makhsun; T. Sakuma; E. Kartini (Jurnal Sains Materi Indonesia, 2014)
CHARACTERISTIC OF (AgI)0.44 (LiI)0.22 (AgPO3)0.34 IONIC CONDUCTOR PREPARED BY MELT QUENCHING METHOD. Characterization of (AgI)0.44 (LiI)0.22 (AgPO3)0.34 ionic conductor prepared by melt quenching method have been carried out by using X-RayDiffractometer (XRD), Differential Scanning Calorimeter (DSC) and Inductance (L) Capacitance (C) Resistance (R) meter. X-ray diffraction pattern shows that the compound has a mixture of amorphous and small amount of crystalline formwith several Bragg peaks correspond toAgI. The DSC thermograph shows that an endothermic peak at temperature ~420 K matches with the phase transition ofAgI which reinforces that a number ofAgI are not dissolved in the material of (AgI)0.44 (LiI)0.22 (AgPO3)0.34 . The obtained dc ionic conductivity is around ~10-2 S/cmat ambient temperature. The activation energy has two values, 0.20 eV below ~380 K and 0.15 eV above ~380 K.